‫הדגמת הוכחת משפט‬    ‫פיתגורס‬
a       b                    ab                    ba        b       a
S ABCD = (a + b) = a + 2ab + b                  2       2           2          a           b                              ...
a       b                    ab                    ba        b       a
a       b                    ab                    ba        b       a
a       b                c       ab   c                        b                    ca       c            b       a
a ⋅bS ABCD   = 4⋅      + c 2 = 2ab + c 2               2             a         b                       c        a b       ...
a ⋅bS ABCD = (a + b) = a + 2ab + b              2       2          2                                             S ABCD   ...
הדגמת משפט פיתגורס
הדגמת משפט פיתגורס
הדגמת משפט פיתגורס
Upcoming SlideShare
Loading in …5
×

הדגמת משפט פיתגורס

981 views

Published on

0 Comments
0 Likes
Statistics
Notes
  • Be the first to comment

  • Be the first to like this

No Downloads
Views
Total views
981
On SlideShare
0
From Embeds
0
Number of Embeds
2
Actions
Shares
0
Downloads
2
Comments
0
Likes
0
Embeds 0
No embeds

No notes for slide

הדגמת משפט פיתגורס

  1. 1. ‫הדגמת הוכחת משפט‬ ‫פיתגורס‬
  2. 2. a b ab ba b a
  3. 3. S ABCD = (a + b) = a + 2ab + b 2 2 2 a b a b b a b a
  4. 4. a b ab ba b a
  5. 5. a b ab ba b a
  6. 6. a b c ab c b ca c b a
  7. 7. a ⋅bS ABCD = 4⋅ + c 2 = 2ab + c 2 2 a b c a b c b c a c b a
  8. 8. a ⋅bS ABCD = (a + b) = a + 2ab + b 2 2 2 S ABCD = 4⋅ + c 2 = 2ab + c 2 2 a + 2ab + b = 2ab + c 2 2 2 a + 2ab + b = 2ab + c 2 2 2 a +b2 2 =c 2

×